Drilling Cores and Geophysical Characteristics of Gas Hydrate-Bearing Sediments in the Production Test Region in the Shenhu sea, South China sea - Liang, Jin; Meng, Miaomiao; Liang, Jinqiang; Ren, Jinfeng; He, Yulin; Li, Tingwei; Xu, Mengjie; Wang, Xiaoxue (Frontiers in Earth Science, 2022)
Gas hydrate production testing was conducted in 2017 in the Shenhu Area in the northern part of the South China Sea, and unprecedented success was achieved. In order to obtain gas production and physical properties of gas hydrate reservoirs in the study area and determine the location of test production wells, the seismic and logging data and drilling cores were analyzed in detail, the physical characteristics of the sediments, faults, gas components, and reservoir were studied. The results show that (1) the gas hydrates are diffusion type, with reservoirs dominated by clayey silt sediments, and the gas hydrate-bearing layers are characterized by soup-like, porridge-like, cavity, and vein structures; (2) the resistivity and acoustic velocity of gas hydrate formation are significantly higher than those of the surrounding sediments, while the neutron porosity, density, and natural gamma are slightly lower; the Bottom Simulating Reflectors (BSRs) in seismic profiles exhibit the exist of gas hydrates; (3) gas chimneys and fault channels are well-developed beneath the BSRs, and hydrocarbon gases can easily migrate into the gas hydrate reservoirs in areas with stable temperature and pressure conditions; (4) the gas hydrate saturation is high, the highest saturation in site W17 was up to 76%, with an average of 33%; while the highest saturation in site W19 was up to 68%, with an average of 31%. The gas source is considered as mixed gas of thermogenic gas and microbial gas. By comparing the core samples and geophysical characteristics of sites W17 and W19 in the study area and calculating the thickness, distribution area, and saturation of the hydrate deposition layer, it was found that site W17 is characterized by a thick layer, large area, high saturation, and good sealing, and thus, site W17 was established as the test production site. The development of gas chimney and faults provides driving force for the upward migration of deep gas, and the gas migrates to gas hydrate stable zone in forms of diffusion, water soluble and free state, forming high saturation of diffusion gas hydrates.